ANALISIS PASSWORD CRACKCING MNEGGUNAKAN GPU PROCESS - Joko Dwi Santoso (Jurnal Mantik Penusa)
Data security is one thing that will not be lost in line with the development of digital technology. One of the simplest data security methods is providing passwords or keywords to the data that we want to secure from the hands of irresponsible people. Even so this method does not fully guarantee that our data will not be hacked by hackers because they already have many techniques to break through this security. One way is to use brute force techniques. In this paper, researchers are observing how much influence overclocking a computer graphics card when it is used to do password cracking. The results of the analysis will be useful for optimizing computer graphics cards for password cracking. As well as this analysis is expected to be used as a reference to learn more about computer hardware systems and data security.